Pesquisa Etnográfica : desvendando os significados culturais de uma professora e seus alunos sobre a língua inglesa e seu aprendizado - LUZ, Rosângela Medeiros da (2010)
This ethnographic research sought to identify and understand how English language learners in a higher technology course in the business field attributed cultural meanings to the English language and its teaching and learning, and investigated how these cultural meanings interfered with the classroom dynamics. Some examples of this interference could be seen in the resistance of students towards the language taught, on the various forms of social interaction in the group during class, and in the resistance towards the methodology adopted by the teacher in the classroom, since there were comments from students about "ideal model / methodology for teaching foreign language (FL). This study took the form of participant observation, in which behavior, communication, actions and / or events of learners in the English classroom were observed and recorded and analyzed in order to identify the cultural domains, through the analysis of semantic relationship offered by Spradley (1980), and thus reveal the cultural meanings to such attitudes and behaviors, those cultural explanations have been built on the foundation of the emic principle, common in ethnographic studies. Through the analysis we realized that there were different cultural understandings about what was learning to the teacher and to her students. These cultural differences resulted in conflicts about the expectations regarding to the roles that these participants should take in the foreign language classroom, while the teacher envisioned an autonomous and active student, the students, on their turn, presented themselves as free of charge from this complex process of learning a FL, since, attributed this responsibility to others. As most of the problems, which arose in this investigated context, were related to cultural conflicts, especially the ones regarding the culture of teaching and learning the English language, we discussed the importance of an intercultural approach in the teaching practice of EFL teachers so they can mediate this mix of culture that can take place in the classroom. In order to achieve that, we reflected on the ethnorelativism stance, suggested by the model DIMS from Bennett (1993), and on the roles of teachers and students presented by Santos (2004). Finally, this study sought to reveal the cultural factors, that even in an invisible dimension, impel the dynamics of the classroom, in other words, we attempted to unravel what underlies teaching and learning of the English language in that investigated context.